2020
DOI: 10.1186/s40902-020-00271-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the hyoid bone, tongue, and oropharyngeal airway space after mandibular setback surgery evaluated by cone-beam computed tomography

Abstract: Background: Mandibular setback surgery can change the position of the mandible which improves occlusion and facial profile. Surgical movement of the mandible affects the base of the tongue, hyoid bone, and associated tissues, resulting in changes in the pharyngeal airway space. The aim of this study was to analyze the 3-dimensional (3D) changes in the hyoid bone and tongue positions and oropharyngeal airway space after mandibular setback surgery. Methods: A total of 30 pairs of cone-beam computed tomography (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…Additionally, alternations of hyoid bone position after orthognathic operations have been reported. The hyoid position moves upward after mandibular advancement surgery and downward after mandibular setback surgery [ 12 , 13 ]. Mortazavi et al revealed that in skeletal class III with mandibular prognathism, the hyoid bone is positioned more anteriorly than in class I and II.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, alternations of hyoid bone position after orthognathic operations have been reported. The hyoid position moves upward after mandibular advancement surgery and downward after mandibular setback surgery [ 12 , 13 ]. Mortazavi et al revealed that in skeletal class III with mandibular prognathism, the hyoid bone is positioned more anteriorly than in class I and II.…”
Section: Discussionmentioning
confidence: 99%
“…las condiciones faciales a nivel de tejidos blandos y tejidos duros. 12,13 Se ha indicado 14 que la posición del hueso hioides no es constante, y que depende de las relaciones anteroposteriores maxilomandibulares. En la presente investigación se observó una correlación significativa entre la posición anteroposterior de la mandíbula, el ángulo mandibular y la posición del hueso hioides; en los sujetos clase II facial se relacionó la posición retrognática mandibular con el aumento en el ángulo del plano mandibular y aumento en la distancia del ángulo mandibular al hueso hioides en comparación con lo observado en los sujetos clase III facial.…”
Section: Wwwmedigraphicorgmxunclassified
“…On the other hand, X-ray [ 18 , 19 , 20 ] and CT [ 21 , 22 , 23 , 24 , 25 ] systems are cheaper than MRI, they have a reasonable resolution, and they have many applications as well. X-ray is used for tongue contour extraction [ 26 , 27 ]; it is also used for tongue contour image synthesis to create articulation copy [ 28 ] or combining physiological models to fit X-ray images.…”
Section: Introductionmentioning
confidence: 99%